Draft Special Component Plan 1986-87 - Planning Commission (Planning Commission, 1986)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, K^raikal, Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on-the east coast about 160 Kms. south of Madras is the largest of these and consists of 12 scattered areas interspearsed with enclaves of south' Arcot District of Tamil N^du. Karaikal region is about 140 Kms. South of Pondicherry and it is surrounded by Thanjavur District of Tamil Nadu Y?nam region is located about 650 Kms. north of Madras near Kakinade in Andhra Pradesh. Mahe region is on the west coast near Teiiicherry in Kerala.
Union Territory of Pondicherry